(untitled) (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2022)
Rapid technological developments in business, office administration, government, and information dissemination play an important and major role in human life as a whole. The internet is a supporting tool as a source of information in finding information related to various activities. Sumberagung Village has quite a large natural potential such as plantations, agriculture, and animal husbandry but is not widely known by people outside the village. The Village Website is expected to be a means of disseminating information, supporting superior village programs and publishing matters related to the potential in Sumberagung Village. Until now, the community or village officials in Sumberagung Village have minimal use of websites, so the dissemination of village information through the website has not been optimally implemented. The PKM approach with Participatory Action Research (PAR) is an approach whose process aims to learn to overcome problems and meet the practical needs of the community, as well as the production of knowledge. PKM activities were carried out in October 2022. Several stages have been carried out in the activity; Coordination with partners, Preparation of website creation, program implementation, and mentoring. This training activity provides direct experience to village officials in operating the Sumberagung village website. The results of the skills assessment of village officials showed that 70% of training participants had good skills when operating the Sumberagung village website. As many as 30% of training participants were in the category with fairly good skills. It is hoped that village programs and information about the village can be accessed and socialized properly. Â